Influence of Niobium on the Beginning of the Plastic Flow of Material during Cold Deformation - Stoja Rešković; Ivan Jandrlić (The Scientific World Journal)
Investigations were conducted on low-carbon steel and the steel with same chemical composition with addition of microalloying element niobium. While tensile testing was carried out, the thermographic measurement was tacking place simultaneously. A specific behavior of niobium microalloyed steel was noticed. Test results have shown that, in the elastic deformation region, thermoelastic effect occurs, which is more pronounced in niobium microalloyed steel. Start of plastic flow in steel which is not microalloyed with niobium begins later in comparison to the microalloyed steel, and it is conducted so that, at the point of maximum stress, deformation zone is formed within which stresses grow. In steel microalloyed with niobium after proportionality limit, comes the occurrence of the localized increase in temperature and the occurrence of Lüders band, which propagate along the sample forming a deformation zone.